Legal Protection for Land Rights Holders Designated as Abandoned Land - Wardah, Elok Oktavia; Michael, Tomy; Lyanthi, Merline Eva (CV. Era Digital Nusantara, 2025)
This article discusses the legal protection for lands right holder designated as abandoned lands. Abandoned land in Indonesia poses serious challenges, not only for the rights holders but also for the development of society and the states. This research employs a normative legal research method to analyzes applicable legal provision and implications of the regulations of abandoned land on rights holders and the wider community. The findings indicate that land rights holders have an obligation to manage and utilize their land in accordance with the prevailing regulations. Failure to do so may result in the designation of their land as abandoned, subsequently transferring its status to that controlled by the state. Additionally, this article recommends measures to enhance legal protection for rights holders, including the application of good governance principles in addressing abandoned land issues. These findings provide important insights into the need for more effective regulations and actions in managing abandoned land for the welfare of the communition and the states.